Impact of Hemoglobin and Iron Deficiency on Mortality in Patients with Acute Myocardial Infarction in Intensive Care Units: A Retrospective Study from MIMIC-IV - Fangyuan Luo; Zhe Wang; Tong Gao; Baofu Wang; Yijie Gao; Mengru Liu; Hong Jiang; Xianlun Li (Reviews in Cardiovascular Medicine)
Background: Anemia and iron deficiency (ID) are common in patients with acute myocardial infarction (AMI), especially those in intensive care units (ICU). This study investigated the impact of hemoglobin (Hb) and ID on the short-term mortality of critically ill patients with AMI. Methods: Overall 992 AMI patients with their first ICU admission were included in this analysis. ID was defined as serum ferritin <100 ng/mL or transferrin saturation (TSAT) <20%. Patients were categorized into four groups according to their Hb concentrations and the presence of ID. Kaplan-Meier survival analysis was used to assess differences in all-cause mortality between the different groups, and Cox regression models to identify risk factors for all-cause mortality. Results: Anemia was present in 89.5% of patients, while 65.9% suffered from ID. Patients in the group with Hb <9 g/dL and without ID were the youngest, yet they exhibited the highest severity scores. The Kaplan–Meier analysis showed that this group had a higher rate of all-cause mortality compared to the other three groups (Log-rank test p = 0.005). Moreover, multivariate Cox regression analysis revealed that Hb <9 g/dL and no ID was associated with a higher risk of all-cause mortality at 120 days (hazard ratio 1.512, 95% confidence interval 1.031–2.217, p = 0.034) when compared to the reference group (Hb ≥9 g/dL and no ID). Additionally, multivariate Cox regression analysis showed that lower Hb was linked to increased rates of all-cause mortality at 30, 60, 90, and 120 days. Elevated levels of ferritin and TSAT were also associated with increased all-cause mortality at 60, 90, and 120 days. Compared to patients without ID, those with ID had a decreased risk of all-cause mortality at 60, 90, and 120 days. Conclusions: Anemia and ID were prevalent in ICU patients with AMI. Patients with Hb <9 g/dL and without ID showed higher 120-day all-cause mortality. Additionally, lower Hb, elevated ferritin, and increased TSAT levels were identified as significant risk factors for short-term all-cause mortality in these patients.